Penentuan Model Kesetimbangan Adsorpsi Ion Fosfat (PO4-3) Menggunakan Arang Aktif Tongkol Jagung Dengan Variasi Massa Arang Aktif Dan Kecepatan Pengadukan - Nainggolan, Ira Tri Asi Br.; Herman, Syamsu; Yenti, Silvia Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One of contamination of laundry liquid waste containing phosphate causes negative impact on society lives. One of efforts to reduce phosphate in laundry wast is adsorption process. The purpose of this study is to find out the effect of absorbent active charcoal mass from the corn cobs and stirring speed and to determine the equilibrium model for phosphate adsorption.First, to determine the equilibrium time with 2 grams of active charcoal in a beaker glass with Na3PO4 solution ( 100 mL ) with 200rpm stirring speed, equilibrium time has been obtained before other variables.The more active charcoal mass of corn cobs and stirring speed of adsorption, the less reaming of phosphate concentration.At 100 rpm speed, 1 gram mass, 2 grams and 3 grams of phosphate concentration after 7,105 ppm, 5,521 ppm, 5,015 ppm absorption.At 200 rpm stirring speed for 1 gram mass, 2 grams and 3 grams of phosphate concentration after 7,065 ppm, 4,474 ppm and 2,134 ppm. At 300 rpm stirring speed for 1 gram mass, 2 grams and 3 grams of phosphate concentration after 5,140 ppm, 3,121 ppm and 2,090 ppm absorption. The mechanism of phosphate adsorption of corn cobs active charcoal powder is compatible with Freundlich Isotherm model which represents the physical adsorption with (R2) 0,999 factor correlation value.Keywords : adsorption, active charcoal, laundry waste, phosphate, equilibrium model.